Kykot V. M. Translation as poem image structure transformation - Kykot V. M. (Philological Treatises, 2020)
The article deals with the structural nature of poetic image and poetic translation as poem structure transformation as well. The process of verse translation is considered as poem image structure transformation by way of its components relationship reconstruction